The Effect of Family Wealth on Physical Function Among Older Adults in Mpumalanga, South Africa: A Causal Network Analysis - Keletso Makofane; Lisa F. Berkman; Mary T. Bassett; Eric J. Tchetgen Tchetgen; Eric J. Tchetgen Tchetgen (Frontiers Media S.A., 2023)
Objectives: The aging of the South African population could have profound implications for the independence and overall quality of life of older adults as life expectancy increases. While there is evidence that lifetime socio-economic status shapes risks for later function and disability, it is unclear whether, and how, the wealth of family members shapes these outcomes. We investigated the relationship between outcomes activities of daily living (ADL), grip strength, and gait speed, and the household wealth of non-coresident family members.Methods: Using data from Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa (HAALSI) and the Agincourt Health and Demographic Surveillance System (AHDSS), we examined the relationship between physical function and household and family wealth in the 13 preceding years. HAALSI is a cohort of 5,059 adults who were 40 years or older at baseline in 2014. Using auto-g-computation-a recently proposed statistical approach to quantify causal effects in the context of a network of interconnected units-we estimated the effect of own and family wealth on the outcomes of interest.Results: We found no evidence of effects of family wealth on physical function and disability.Conclusion: Further research is needed to assess the effect of family wealth in early life on physical function and disability outcomes.